Uwagi o genezie i koncepcjach metafilozofii - Szubka, Tadeusz (Człowiek i Społeczeństwo, 2022)
Although reflection on the nature of philosophy has constituted an integral part of this discipline from its beginnings, the term „metaphilosophy” referring to such a reflection only made its first appearance in the middle of the twentieth century. In the course of discussions concerning the book by C.J. Ducasse about the subject-matter and method of philosophy, the term was introduced in the United States by C.G. Hempel and M. Lazerowitz, and in Poland by M. Choynowski. Subsequently, two different metaphilosophical programs, which disseminated this category, were put forward by Lazerowitz and J. Kalinowski. They had dissimilar objectives and assumptions, though for both of them a crucial problem was the diversity of philosophical conceptions and persistent disagreements in philosophy.